In Vitro Ruminal Fermentation and Degradability of Rice Husk on Rice Bran Substitution - Rusli Fidriyanto; Roni Ridwan; Wulansih Dwi Astuti; Rohmatussolihat Rohmatussolihat; Nurul Fitri Sari; Muh Watman; Yantyati Widyastuti (ANNALES BOGORIENSES, 2020)
Rice bran is a by-product of the rice milling process and has been well used as livestock feed. Rice bran is often adulterated with rice husk. The objective of this study was to evaluate the in vitro ruminal fermentation characteristics of rice bran with various compositions of rice husk and assess the relationship between rice husk addition and rice bran quality. The experiment was arranged in a completely randomized design with rice husk addition as a factor and three replications. Data of proximate value, gas production, ruminal degradability, and volatile fatty acid production were analyzed by analysis of variance. Moreover, significant effects of each treatment in the in vitro fermentation were further analyzed by Duncan's multiple range test (P<0.05). It was shown that the addition of rice husk to rice bran could increase acetic acid level, but it reduced potential gas production, gas production rate, organic matter and dry matter digestibility, and propionic acid level. Interestingly, the linear regression of dry matter digestibility, organic matter digestibility, and potential gas production showed the high adjusted R2 values. Moreover, this study also revealed that 10% of rice husk substitution on rice bran could significantly reduce the dry matter digestibility.